On the plains in '65 : the 6th West Virginia Volunteer Cavalry in the West - Holliday, Geo. H. (George Hayes), 1847-1919 (War and society in North America (Athens, Ohio), 2021)
"This annotated edition of Holliday's recollections-known primarily among historians of the American West-re-contextualizes his memoir to include his boyhood in southern Ohio and the largely untold story of the hundreds of Buckeyes who crossed the Ohio River to serve their country in Virginia (later West Virginia) regiments, ultimately traveling across Kansas, Nebraska, Colorado, and Wyoming to safeguard mail and stage routes along the celebrated Oregon Trail during a pivotal time in American history. Glenn Longacre's extensive research in federal, state, and local archives, manuscript collections, and period newspapers complements his correspondence with the living descendants of Holliday and other soldiers to integrate this story deservedly as part of Appalachian history before, during, and after the Civil War. From this perspective it addresses an entirely new audience within Appalachian Studies, Civil War and frontier history enthusiasts, students, and the general public"--